Values and clean sport. Issue 5 (4th March 2021) - Mortimer, Hannah; Whitehead, Jean; Kavussanu, Maria; Gürpınar, Bahri; Ring, Christopher
ABSTRACT: The spirit of sport, which encompasses intrinsic values associated with sport participation, is core to the World Anti-Doping Agency's (WADA) strategy for doping prevention. The contribution of these values to clean sport has yet to be established. In this study, athletes rated the importance of spirit of sport values (WADA, 2015) and sport values (Lee et al., 2000, 2008) and indicated their clean sport likelihood in a hypothetical scenario. Clean sport likelihood was positively predicted by the five spirit of sport values (ethics/fair play/honesty, respect for rules/laws, dedication/commitment, teamwork, community/solidarity), two sport value domains (morality, competence), and 11 sport values (contract maintenance, being fair, conscientiousness, sportspersonship, show skills, health/fitness, caring/compassion, team cohesion, achievement, tolerance, obedience). Clean sport likelihood was best predicted by moral values.